THE INFLUENCE OF ISLAMIC BANK FINANCING ON ECONOMIC GROWTH IN OIC COUNTRIES: A FIRST DIFFERENCE–GENERALIZED METHOD OF MOMENTS APPROACH) - Ayu Rahmiyati; Siti Zulaikha; Nurrizka Puji Lestari; Eko Kurniawan; Tanza Dona Pertiwi (Jurnal Ekonomi dan Bisnis Airlangga, 2026)
Introduction: The rapid expansion of Islamic finance in Organization of Islamic Cooperation (OIC) countries raises an important question regarding its contribution to economic growth, as prior studies report mixed evidence. Methods: This study uses panel data from 15 OIC countries over 2014–2023 with a quantitative approach. Control variables include institutional quality, foreign direct investment, human development index, population, and trade openness. The first-difference generalized method of moments (FD-GMM) is applied to address endogeneity. Results: The empirical results show that Islamic bank financing has a positive and statistically significant effect on economic growth in both the short and long term. Additionally, institutional quality and human development are found to play a significant role in shaping economic growth dynamics across OIC countries. Conclusion and suggestion: The findings underscore the strategic importance of Islamic bank financing in strengthening the real sector, enhancing financial inclusion, expanding access to productive financing, and supporting capital accumulation. Therefore, this study suggests strengthening governance quality, improving human development outcomes, optimizing the allocation of productive Islamic financing, and promoting deeper integration between the Islamic financial sector and the real economy to foster inclusive and sustainable economic growth in OIC countries.